الجريمة الحضرية - مداح حمدان (University of Eloued جامعة الوادي, 2024)
ملخص: تتناول هذه الدراسة قراءة سوسيوإيكولوجية ميدانية للجريمة الحضرية في الأقطاب الحضرية الجديدة بولاية عنابة، لاحظ الباحث مشكلة الجريمة تزداد مع نمو التحضر، وتنتشر الجرائم مثل العنف المنزلي والاغتصاب والقتل والجرائم الإلكترونية والجريمة الاقتصادية، خلصت الدراسة إلى أن الجريمة تميل إلى استخدام الشباب الجانحين كقوة عاملة ورخيصة، مما أدى إلى توطيد ثقافة فرعية للعصابات متجذرة، قام الباحث بدراسة حالة لعينة من ثلاثة أفراد، من سكان الأقطاب الحضرية الجديدة، فمكافحة العنف يجب أن تشمل الجهات الفاعلة المعنية كالمحاكم، والتعليم، والإسكان، والصحة، وأن أسبابها هي: عدم المساواة، ونقص الدعم للأحياء، وعدم الوصول الحقيقي إلى الخدمات، وتأثير التنقل السكني في الأحياء على الجريمة، وعواقب تجارب السكان مع الجريمة على إحساسهم بالارتباط بالحي. Abstract: . This study examines a field socio-ecological reading of urban crime in the new urban poles of Annaba State crime problem increases as urbanization grows, and crimes such as domestic violence, rape, murder, cybercrime and economic crime are widespread the study found that crime tended to use young offenders as a labour force and cheap, Leading to the consolidation of a deep-rooted gang subculture, the researcher conducted a case study of a sample of three individuals, Among the inhabitants of the new urban poles, combating violence must include relevant actors such as courts, education, housing and health, the causes of which are: Inequality, lack of support for neighbourhoods, lack of genuine access to services, the impact of neighbourhood housing mobility on crime and the consequences of people's experiences of crime on their sense of connection with the neighbourhood.
قراءة سوسيوإيكولوجية ميدانية في الأقطاب الحضرية الجديدة بعنابة
Keywords: جريمة حضرية; أقطاب حضرية; عنابة; urban crime; urban poles; Annaba